2022
DOI: 10.1155/2022/2832400
|View full text |Cite|
|
Sign up to set email alerts
|

FVC-NET: An Automated Diagnosis of Pulmonary Fibrosis Progression Prediction Using Honeycombing and Deep Learning

Abstract: Pulmonary fibrosis is a severe chronic lung disease that causes irreversible scarring in the tissues of the lungs, which results in the loss of lung capacity. The Forced Vital Capacity (FVC) of the patient is an interesting measure to investigate this disease to have the prognosis of the disease. This paper proposes a deep learning-based FVC-Net architecture to predict the progression of the disease from the patient’s computed tomography (CT) scan and the patient’s metadata. The input to the model combines the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We found that PBMC adrenomedullin levels in DM patients with ILD associated with pulmonary function test results, higher adrenomedullin mRNA levels correlated with worse lung function in DM patients with ILD, which may help assess the severity of ILD ( 33 , 34 ). In addition, deterioration of lung function, especially forced vital capacity (FVC) and DLco, is known to indicate disease progression and to be corelated with prognosis in DM patients with ILD ( 34 ).…”
Section: Discussionmentioning
confidence: 80%
“…We found that PBMC adrenomedullin levels in DM patients with ILD associated with pulmonary function test results, higher adrenomedullin mRNA levels correlated with worse lung function in DM patients with ILD, which may help assess the severity of ILD ( 33 , 34 ). In addition, deterioration of lung function, especially forced vital capacity (FVC) and DLco, is known to indicate disease progression and to be corelated with prognosis in DM patients with ILD ( 34 ).…”
Section: Discussionmentioning
confidence: 80%
“…The authors also used the GSInquire method 35 to make the model more explainable concerning its predictions. Yadav et al 36 designed FVC-Net, a deep learning-based architecture, to predict the progression of the disease from the patient's CT scans and the patient's metadata. The proposed method performs lung segmentation and returns a score for the degree of honeycombing.…”
Section: Regression Tasksmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%